2017
DOI: 10.1021/acs.chemmater.7b02845
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Microphase Separation and Synergistic Permeability in Stacked Lipid–Polymer Hybrid Membranes

Abstract: We present new structures of soft-material thin films that augment the functionality of substrate-mediated delivery systems. A hybrid material composed of phospholipids and block copolymers adopts a multilayered membrane structure supported on a solid surface. The hybrid films comprise intentional intramembrane heterogeneities that register across multilayers. These stacked domains convey unprecedented enhancement and control of permeability of solutes across micrometer-thick films. Using grazing incidence X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 113 publications
3
43
1
Order By: Relevance
“…To understand the self-assembly and molecular organization of mPEG-b-PCL and DPPC within a hybrid membrane we performed structural studies using Small and Wide Angle X-ray scattering (SAXS/WAXS). While PL alkyl chain packing has been investigated in PL-BCP hybrid membranes before [6,12,[14][15][16], in nearly all systems studied so far the BCP component remains amorphous. In this paper, we wanted to investigate the behavior of a PL-BCP hybrid membrane when the BCP component has the ability to crystallize.…”
Section: Dppc-mpeg-b-pcl Hybrid Membrane Structure and Molecular Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the self-assembly and molecular organization of mPEG-b-PCL and DPPC within a hybrid membrane we performed structural studies using Small and Wide Angle X-ray scattering (SAXS/WAXS). While PL alkyl chain packing has been investigated in PL-BCP hybrid membranes before [6,12,[14][15][16], in nearly all systems studied so far the BCP component remains amorphous. In this paper, we wanted to investigate the behavior of a PL-BCP hybrid membrane when the BCP component has the ability to crystallize.…”
Section: Dppc-mpeg-b-pcl Hybrid Membrane Structure and Molecular Ordermentioning
confidence: 99%
“…In the recent years, hybrid PL–BCP membranes have indeed emerged [ 6 , 7 , 9 , 10 , 11 , 12 ] as materials where the combined properties are not merely an additive of those observed in pure components. For example, the dynamics of alkyl chain conformational changes in 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) membranes are enhanced at room temperature by hybridization with poly(butadiene)- b -poly(ethylene oxide)—PBD-PEO BCPs [ 6 , 12 ]. In addition, DPPC membranes in the gel-phase (L β ) hybridized with PBD-PEO in a giant unilamellar vesicle (GUV) exhibit the formation of large phase-separated PL-rich and BCP-rich domains [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, relatively little information is available about the structure, chemical nature, and molar mass of copolymers that could mix ideally with phospholipids. Most commonly, poly(butadiene) [3][4][5][6][7][8][9][10][11][12] and poly(dimethylsiloxane) [13][14][15][16][17][18][19][20] have been used as hydrophobic block, while studies with poly(isobutene) [21][22][23], poly(caprolactone) [24,25], poly(isoprene) [26], and poly(laurylacrylate) [27] have also been reported. Poly(ethylene oxide) is by far the most used hydrophilic block, although few studies report the use of hydrophilic thermo-responsive blocks such as poly(2-isopropyl-2-oxazoline) [28] and poly(ethylene glycoldiacrylate) [27].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it is imperative to obtain uniform lung membrane film thickness. We have shown that lipid film thickness, even for complex mixtures, can be controlled by spin-coating speed [45][46][47] . The thickness and morphology of lung membranes can be determined by AFM using the tip-scratch method (Fig.…”
Section: Resultsmentioning
confidence: 95%